The Design and Implementation of the VRPML Support Environments - Zamli, Kamal Zuhairi; Mat Isa, Nor Ashidi; Khamis, Norazlina (Malaysian Journal of Computer Science, 2005)
Software processes relate to the sequences of steps that must be performed by software engineers in order to pursue the goals of software engineering. In order to have an accurate representation and implementation of what the actual steps are, software processes may be modelled and enacted by a Process Modelling Language (PML) and its process support system (called the Process Centered Environments i.e. PSEE). This paper discusses the design of the process support environment for a new process modelling language, called the Virtual Reality Process Modelling Language (VRPML). It identifies the main components of the VRPML process support environments as well as summarises the current implementation prototypes. It highlights lessons learned and offers insights into the design of next-generation PMLs and PSEEs.